2014
DOI: 10.1002/chin.201438023
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: A Facile Synthesis and Characterization of Sodium Bismuth Sulfide (NaBiS2) under Hydrothermal Condition.

Abstract: A Facile Synthesis and Characterization of Sodium Bismuth Sulfide (NaBiS 2) under Hydrothermal Condition. -Nanosheets of the title compound are hydrothermally synthesized as the sole product from mixtures of Bi(NO 3)3, L-cysteine, NaOH, and H2O (autoclave, 180 C, 72 h, 46% yield). The samples are characterized by XRD, SEM, diffuse reflectance spectrophotometry, and XPS. The environmentally benign preparation method might be useful in a variety of fields, including thermoelectric and light harvesting materials… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…NaLaS 2 and NaBiS 2 materials have a cubic NaCltype structure where the sulfur occupies the chlorine sublattice, while cations (Na and La/Bi) statistically occupy the Na sublattice as a solid solution. 12,27,47 The final mass yields were ∼86 and ∼90% based on lanthanum and bismuth, respectively. The single-phases of NaLa 1−x Bi x S 2 solid solutions were obtained by varying the molar ratio of Bi to La; there was no impurity phase.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…NaLaS 2 and NaBiS 2 materials have a cubic NaCltype structure where the sulfur occupies the chlorine sublattice, while cations (Na and La/Bi) statistically occupy the Na sublattice as a solid solution. 12,27,47 The final mass yields were ∼86 and ∼90% based on lanthanum and bismuth, respectively. The single-phases of NaLa 1−x Bi x S 2 solid solutions were obtained by varying the molar ratio of Bi to La; there was no impurity phase.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…11 Experiments showed that ABiS 2 (A = Li, Na, and K) crystallize as compounds with a disordered NaCl-type cubic structure, 11 and the primary results of NaBiS 2 showed an optical band gap of ∼1.2 eV. 12 This band gap falls within the ideal range for photovoltaic solar cell requirements or tandem cells. 8,13 However, this band gap is often too small for photocatalytic overall water splitting.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation